Cell differentiation versus cell death: extracellular glucose is a key determinant of cell fate following oxidative stress exposure - Hulley, P; Poulsen, R; Carr, A; Knowles, H (Nature Publishing Group, 2014)
Cells, particularly mechano-sensitive musculoskeletal cells such as tenocytes, routinely encounter oxidative stress. Oxidative stress can not only stimulate tissue repair, but also cause damage leading to tissue degeneration. As diabetes is associated with increased oxidative damage as well as increased risk of tendon degeneration, the aim of this study was to determine if extracellular glucose levels alter the response of tendon cells to oxidative stress. Primary human tenocytes were cultured in either high (17.5 mM) or low (5 mM) glucose and treated with 100 μM hydrogen peroxide. In low glucose, peroxide-treated cells remained fully viable and collagen synthesis was increased, suggesting an anabolic response. In high glucose, however, peroxide treatment led to increased bim-mediated apoptosis. The activities of both forkhead box O (FOXO1) and p53 were required for upregulation of bim RNA expression in high glucose. We found that both p53-mediated inhibition of the bim repressor micro RNA (miR17-92) and FOXO1-mediated upregulation of bim transcription were required to permit accumulation of bim RNA. High glucose coupled with oxidative stress resulted in upregulation of miR28-5p, which directly inhibited expression of the p53 deacetylase sirtuin 3, resulting in increased levels of acetylated p53. In peroxide-treated cells in both high and low glucose, protein levels of acetylated FOXO1 as well as HIF1α (hypoxia-inducible factor 1α) were increased. However, under low-glucose conditions, peroxide treatment resulted in activation of p38, which inhibited FOXO1-mediated but promoted HIF1α-mediated transcriptional activity. In low glucose, HIF1α upregulated expression of sox9 and scleraxis, two critical transcription factors involved in establishing the tenocyte phenotype, and increased collagen synthesis. The switch from FOXO1-mediated (proapoptosis) to HIF1α-mediated (prodifferentiation) transcription occurred at an extracellular glucose concentration of 7 mM, a concentration equivalent to the maximum normal blood glucose concentration. Extracellular glucose has a profound effect on the cellular response to oxidative stress. A level of oxidative stress normally anabolic may be pathological in high glucose.